NILAI NILAI KEARIFAN LOKAL DALAM TRADISI KEKICERAN MASYARAKAT PUGUNG PESISIR BARAT LAMPUNG - Ulfa, Siti Tiara; Ariyani, Farida; Astriawan, Deris (Jurnal Tiyuh Lampung: Pendidikan Bahasa dan Kebudayaan, 2023)
In the Saibatin Marga Pugung community, there are traditions and ways to preserve Lampung culture. They use the momentum of Eid as a place to apologize en masse and introduce Lampung culture to the wider community. This tradition is called Kekiceran. The Kekiceran tradition is a cultural art performance performed by muli mekhanai for generations in order to enliven Eid Al-Fitr. This tradition is very strange for people who do not know clearly how the implementation of Kekiceran. In this tradition, of course, there are local wisdom values that we can find. In this study, the author conducted research on the Lampung Saibatin community of Pugung Tampak Clan, North Pesisir District, West Pesisir Regency, Lampung Province. The method used in this research is descriptive method using qualitative data analysis techniques. While the data collection techniques used are interviews, observation and documentation. The results of this study indicate that the Kekiceran tradition is still well implemented and deserves to be known by the wider community because this tradition has functions and uses in order to maintain the original culture of Indonesia, especially Lampung culture. The value of local wisdom contained in it includes 6 aspects, namely religious values, aesthetic values, economic values, educational values, historical values and mutual cooperation values. To find out this tradition can be seen from the implementation process. Based on the results of this study, it can be concluded that the Kekiceran tradition is still carried out today and has three stages in the implementation process, namely the planning stage, the implementation stage and the closing stage and there are also local wisdom values that are owned that must be known by the community.